Mangostins stimulate glucose uptake and inhibit adipocyte differentiation in 3T3-L1 adipocytes - Bakhtiar, M. Taher; Mohamed Amiroudine, Mohamed Zaffar Ali; Darnis, Deny Susanti; Ichwan, Solachuddin J. A.; Kaderi, Mohd Arifin (2012)
Garcinia mangostana (Guttiferae) has interesting biological activities with potential medicinal application. α-mangostin and β-mangostin are the most abundant xanthones isolated from the species. The paper reported the inhibitory effect of the compounds on triglyceride formation, glucose uptake stimulation and gene expression effects on 3T3-L1 adipocytes. Evaluation of the effect of the compounds on triglyceride accumulation was examined by Oil red O staining. The result showed that all compounds inhibited lipid accumulation on 3T3-L1 adipocytes at concentration of 50 μM (P < 0.05) compared to MDI treated cells in a dose-dependent manner. Effect of the cells on uptake of 2-deoxy-D-[3H]glucose was significantly improved by increasing the concentration of the compounds. Analysis of gene expressions by quantitative real-time PCR demonstrated that the compounds inhibited the expression of early adipogenic transcription factor (PPARγ). In addition, the compounds enhanced the expression and plasma membrane translocation of GLUT4 in mature adipocytes. Analysis by using the adipolysis kit showed that α-mangostin particularly increases the free fatty acid release by stimulating the lipolysis pathway. Therefore, these results suggested that α-mangostin and β-mangostin have been found to have a beneficial action in diabetic complications (antiobesity effect) via stimulation of GLUT4 expression and inhibition of PPARγ expression.